Exploring sports interest-talent compatibility among elementary school students - Santri, Aski Ratna; Anggita, Mega; Ali, Mohammad Arif; Sugiarto; Mukarromah, Siti Baitul (UIR Press, 2024)
Background Problems: Every child has interests and talents, but are children’s interests and talents, especially in sports, compatible or similar? This research used scientific selection using the Sports Search test to determine the subject’s sports talent. Research Objectives: This research aims to assess the level of sports interest and talent of elementary school students and identify the suitability of elementary school students’ sports interests and talents. Methods: This type of research is quantitative descriptive research with a survey method. Twenty-two elementary school students were involved as subjects in this research using a purposive sampling technique. Data was collected using surveys, tests, and measurements using instruments like questionnaires and sports search tests. Descriptive statistical analysis was used in this study, and data were expressed in percentages. Findings and Results: The research results were that 95.45% of elementary school students had a high interest in sports, and 4.5.5% had a low interest. As many as 100% of elementary school students have talent in sports. As many as 100% of elementary school students do not have a match between their interests and talents. Conclusion: More in-depth and structured research needs to be carried out in the future to be able to improve students’ performance. Most importantly, it is very important to identify interests and talents from an early age so that there is no mismatch between students’ interests and talents when sports achievement development takes place.